Hutan kita, keputusan kita: sebuah survei mengenai prinsip-prinsip untuk pengambilan keputusan di Malinau - Wollenberg, Eva Karoline; Limberg, G.; Iwan, R.; Rahmawati, R.; Moeliono, M. (Center for International Forestry Research, 2006)
Many people want to improve the governance of forest areas, yet what is considered good governance is not necessarily self-evident or agreed upon by everyone. This study demonstrates the diversity of views held by communities and government officials in Malinau, Indonesian Borneo about what they consider to be good governance. Each group described how they thought decisions about forests should be made, including how to represent interests, allocate land rights, distribute cash benefits from forests, share information and manage forests. Striking differences of opinion among villagers and officials suggest the need for more dialog and discussion about how to coordinate decision-making in Malinau. The results suggest a more general conclusion that defining “good governance” requires an understanding of local contexts and the participation of different groups in determining jointly held principles.